1996
DOI: 10.1200/jco.1996.14.11.2908
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy without irradiation--a novel approach for newly diagnosed CNS germ cell tumors: results of an international cooperative trial. The First International Central Nervous System Germ Cell Tumor Study.

Abstract: Forty-one percent of surviving patients and 50% of all patients were treated successfully with chemotherapy only without irradiation. Chemotherapy-only regimens for CNS GCT, although encouraging, should continue to be used only in the setting of formal clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
175
1
7

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 365 publications
(188 citation statements)
references
References 24 publications
5
175
1
7
Order By: Relevance
“…For nongerminomatous tumors and high-risk germinomas, our response rate (5 of 9) and PFS were comparable to recent reports: 21 of 26 [23], 12 of 18 [24], 21 of 27 [39], 16 of 17 [45]. However, these studies do not clarify whether increased intensification of chemotherapy, with concomitant increased toxicity, improves survival.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…For nongerminomatous tumors and high-risk germinomas, our response rate (5 of 9) and PFS were comparable to recent reports: 21 of 26 [23], 12 of 18 [24], 21 of 27 [39], 16 of 17 [45]. However, these studies do not clarify whether increased intensification of chemotherapy, with concomitant increased toxicity, improves survival.…”
Section: Discussioncontrasting
confidence: 47%
“…CCDP, etoposide, and a VCR were used in this study based on reported response rates for germ cell tumors of the testes [27,28], and of the CNS [21,23,29]. CMP was added due to high response rates reported for single agent CNS treatment [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations